2017
DOI: 10.1007/s12079-016-0367-1
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2 vitamin D3 signalling on immature rat Sertoli cells: gamma-glutamyl transpeptidase and glucose metabolism

Abstract: 1α,25-Dihydroxyvitamin D 3 (1,25-D 3 ) is critical for the maintenance of normal male reproduction since reduced fertility is observed in vitamin D-deficient rats. Gamma-glutamyl transpeptidase (GGT) is a membranebound enzyme that is localized on Sertoli cells and catalyses the transfer of the gamma-glutamyl residues to an amino acid or peptide acceptor. Sertoli cells are also responsible for providing nutrients, as lactate, to the development of germ cells. The aim of this study was to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 74 publications
0
7
1
1
Order By: Relevance
“…Studies that show the analysis of the mitochondrial metabolism of Sertoli cells through sensitive methods are scarce in the literature. With the exception of an earlier study by our group (Gonçalves et al, 2017), no other studies on the analysis of the mitochondrial oxidative metabolism of Sertoli cells through a high-resolution respirometry (OROBOROS) method, as used in the present study, were found. Our data show that Sertoli cells incubated 1 h with 4% effluent showed increased oxygen consumption at the maximum capacity of the ETS state, where they are challenged with sequential titration of FCCP decoupling.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Studies that show the analysis of the mitochondrial metabolism of Sertoli cells through sensitive methods are scarce in the literature. With the exception of an earlier study by our group (Gonçalves et al, 2017), no other studies on the analysis of the mitochondrial oxidative metabolism of Sertoli cells through a high-resolution respirometry (OROBOROS) method, as used in the present study, were found. Our data show that Sertoli cells incubated 1 h with 4% effluent showed increased oxygen consumption at the maximum capacity of the ETS state, where they are challenged with sequential titration of FCCP decoupling.…”
Section: Discussioncontrasting
confidence: 64%
“…We also detected a significant increased effect of effluent in the ROX state. The residual activity in this state is usually represented by partial reduction of oxygen into reactive oxygen species (Gonçalves et al, 2017). In this case, effluent significantly increased the formation of ROS in 10-day-old rat Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding as alterations in paternal chromatin can have dramatic consequences on reproduction especially if the oocyte is unable to repair such paternal nuclear damage. Given the extensive antioxidant and regulatory roles of vitamin D on gene expression, 60‐67 further studies are needed to determine which processes (either in the testis during spermatogenesis or in the epididymis during post‐testicular maturation) could be affected.…”
Section: Discussionmentioning
confidence: 99%
“…7 C). Since LDH is the key enzyme to catalyze the synthesis of lactate from pyruvate under anaerobic condition [ 10 , 30 ], we also checked the activity of LDH in the present study. And the results showed that AA2P (250 μM, 36 h) treatment could increase the activity of LDH significantly (455.05 vs. 424.67; P < 0.01) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Later, SCs are found to be able to secret a variety of molecules, such as growth factors, androgen binding protein (ABP), anti-müllerian hormone (AMH), inhibin B (INHB) and lactate, to provide growth signals and nutrients for spermatogenic cells [ [5] , [6] , [7] ]. Furthermore, multiple exogenous factors are discovered to affect the proliferation, apoptosis and function of SCs, including heat stress [ 8 ], metal [ 7 , 9 ], chemicals [ 5 ] and nutrients [ 10 ], and disturb the subsequent development of germ cells [ 7 ].…”
Section: Introductionmentioning
confidence: 99%